2021
DOI: 10.7759/cureus.19712
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing Kounis Syndrome: A Report of Type 2 Kounis Syndrome and a Brief Review of Management

Abstract: Kounis syndrome is an underdiagnosed medical condition and represents acute coronary syndrome in the setting of allergic reaction. With the increasing prevalence of allergic reactions, more cases of Kounis syndrome are being reported in the literature. Recognizing patients with acute coronary syndrome during an episode of anaphylaxis may be difficult due to symptom overlap; hence, a high index of suspicion must be maintained. This is vital as the management of Kounis syndrome requires meticulous use of medicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…[8]. Однако сообщений о летальных исходах пациентов с СК после внутримышечного введения адреналина нет [9].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…[8]. Однако сообщений о летальных исходах пациентов с СК после внутримышечного введения адреналина нет [9].…”
Section: Discussionunclassified
“…Согласно данным литературы, применение блокаторов Н1-рецепторов, таких как димедрол и хлорфенирамин, не наносит вреда при СК, однако при слишком быстром введении могут привести к гипотензии и снижению тканевой перфузии [9].…”
Section: Discussionunclassified
“…One case also reported a 17-year-old male who suffered from Kounis syndrome due to taking branched-chain amino acid supplements [ 16 ]. We also noted that trigger factors such as contrast agents and food (fish-related products and fruits especially) were present in adult case reports but not in pediatric cases [ 18 - 66 ].…”
Section: Reviewmentioning
confidence: 99%
“…Furthermore, elevated levels of cardiac enzymes, tryptase, and eosinophilia can also serve as indications of Kounis syndrome. In all reported cases involving pediatric patients, ischemic changes (ST elevation and ST depression) were observed on the ECG, except for one case where a 15-year-old patient with Kounis syndrome, due to a wasp sting, displayed normal findings on the ECG [ 34 , 40 , 64 - 66 , 72 , 83 - 90 ]. Similarly, in the case of the adult case reports, it was also observed that ischemic changes were noted on the electrocardiogram (ECG).…”
Section: Reviewmentioning
confidence: 99%
“…According to the most current recommendations, 54 an acute coronary syndrome protocol should be followed in cases of Kounis syndrome type 2 (allergic myocardial infarction). With corticosteroids, antihistamines, vasodilators like nitroglycerin, or Ca2+ Channel blockers, the allergic reaction can be treated as in type 1 syndrome, with an emphasis on the medications' potentially hazardous cardiac side effects.…”
Section: Management Of Type II Kounis Syndromementioning
confidence: 99%